Characteristics of Faceted-Quality Ruby from Longido, Tanzania - Leelawatanasuk, Thanong; Susawee, Namrawee; Bupparenoo, Pimtida (Bulletin of Earth Sciences of Thailand, 2021)
The productions of ruby from major sources such as Thailand, Myanmar and Vietnam were plunged due to the scarcity of nice gem-quality crystals. Among the African countries that supply gem corundum, Longido gem field of Tanzania has been known as the source of low-quality ruby in green zoisite rock (aka Anyolite) which is mainly used for carving or decorative purposes for decades. However, in the mid 2017, there was leak information among gem dealers in Chanthaburi and Bangkok gem markets about a new discovery of faceted-quality ruby from this particular area. In this study, the faceted-quality ruby samples showing quite similar inclusion features seen in ruby from other sources in east Africa but the chemical characteristic is quite unique with relatively high chromium (Cr) content in comparison with ruby from other localities in the same region. Thus, this typical chemical character might be useful for origin determination of ruby from this deposit.